Managing employees undergoing total hip and knee replacement: experiences of workplace representatives - Nouri, Fiona; Coole, Carol; Narayanasamy, Melanie Jay; Baker, Paul; Khan, Sayeed; Drummond, Avril E.R. (Springer, 2018)
Joint replacement is a cost-effective and efficient method of relieving pain, and improving function and health related quality of life, for people with arthritis of the hip and knee [1]. Arthritis-related loss of physical function is associated with unemployment, reduced income and increased sickness absence [2]. In a survey investigating the impact of osteoarthritis (OA), Fautrel et al found that OA has a substantial impact on work, with 20% of patients surveyed still in the workforce and two thirds of those reporting that OA was affecting their work [3]. These factors, in combination with an ageing workforce and changes to the pension age, have resulted in an increase in the number of hip and knee replacements carried out on people of working age over the past ten years. In 2015, 17,293 of 84,462 (20%) hip replacements and 16,121 of 94,437 (17%) knee replacements performed in England, Wales and Northern Ireland were in people aged under 60 years; 25,249 (30%) hip replacements and 32,321 (34%) knee replacements were performed on inpatients aged between 60-69 years [4]. Projections from 2005 suggest that by 2030, the demand for primary total hip (THR) and knee (TKR) replacements will increase by 174% and 673% respectively [5].Consequently return to work (RTW) will be a priority for an increasing proportion of the population following surgery.